IMPACT OF INTERNAL AUDIT AND WHISTLEBLOWING SYSTEMS FROM FRAUD PROTECTION ON BUMN COMPANYS NUMBERED ON THE INDONESIAN SHIPPING BORSE PERIOD 2021-2023 - Yuni Sukandani; Siti Sugihartini; Safira Herian Firdaus; Gintan Regita Maharani; Lailatin Adhimah (International Journal of Economic Integration and Regional Competitiveness, 2024)
A study was conducted to explain how the impact of internal audits and whistleblowing on fraud prevention at BUMN is on the EIB list for 2021–2023. The goal of this study is to explain how the variable x influences the population variable y. Population, i.e., 24 BUMNs that are on the BEI list for the period 2021–2023. Using purposive sampling techniques, the author selected 19 BUMN entities that are on the 2021–2023 BEI list. Double linear regression analysis, hypothesis tests (t and F), classical assumption tests, and determination coefficient tests are the methods applied in this study. Based on the results of the tests, it is known that in the period 2021–2023, internal audit factors and whistleblowing systems will both have a significant influence on the prevention of fraud in the EIB registry.